The effects of on golf drive performance in two groups of golfers with different skill levels - Green, A.; Dafkin, C.; Kerr, S.; McKinon, W. (Biology of Exercise, 2015)
Although walking is a fundamental part of the game of golf, the effects of walking on the golf shots outcome are largely overlooked. The purpose of the present study was to determine the effects of a hole-to-hole distance walk on the golf drive performance as well as possible physiological contributory factors were evaluated. Twenty-one volunteer golfers were recruited and divided into two groups based on their average round scores: More Competitive Golfer (MCG) .88 (n=13) and Irregular Social Golfer (ISG) .89 (n=8). Drive distance was directly measured. Balance and hand-eye coordination were assessed using a modified stork test and a customised three dimensional maze. Participants hit 10 golf balls and then walked 500m before repeating the tests. Heart rates of golfers before driving weren different between groups, but were elevated within the groups following walking. The MCG had longer drives following the walk (p=0.018). The change in the distance was correlated to the change in right leg balance with eyes closed (r=- 0619 p=0.003). Biomechanical changes were correlated to the change in drive distance (r=0.867 p=0.025). This study shows that an aerobic warm-up prior to a round or small amounts of walking early in a round may be beneficial to golfers of better ability.